2013
DOI: 10.3103/s1068375513030083
|View full text |Cite
|
Sign up to set email alerts
|

Electrochemical investigation on the corrosion of 18%Ni M250 grade maraging steel under welded condition in sulfuric acid medium

Abstract: The corrosion behavior of welded maraging steel in sulfuric acid solutions has been studied over a range of acid concentrations and solution temperatures by electrochemical techniques such as Tafel extrap olation and electrochemical impedance spectroscopy. The studies have revealed that the corrosion rate of welded maraging steel increases with the increase in temperature and increase in concentration of sulfuric acid in the medium. The thermodynamic parameters such as activation energy, enthalpy of activation… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(6 citation statements)
references
References 20 publications
0
6
0
Order By: Relevance
“…It can be seen from Table 2 that % IE decreases with increase in temperature in 0.5 M H 2 SO 4. This may be due to decrease in the protective nature of the inhibitive film formed on the metal surface and desorption of the HMBH molecules at higher temperature [22]. The variation of % IE with varying concentrations of HMBH at different temperatures is depicted in Fig.…”
Section: Evaluation Of Kinetic Parametersmentioning
confidence: 99%
“…It can be seen from Table 2 that % IE decreases with increase in temperature in 0.5 M H 2 SO 4. This may be due to decrease in the protective nature of the inhibitive film formed on the metal surface and desorption of the HMBH molecules at higher temperature [22]. The variation of % IE with varying concentrations of HMBH at different temperatures is depicted in Fig.…”
Section: Evaluation Of Kinetic Parametersmentioning
confidence: 99%
“…The corrosion and corrosion protection of maraging steels in different media have been investigated by many researchers . It has been reported that maraging steels show better corrosion resistance in acidic solutions compared to tempered martensite alloy steels.…”
Section: Introductionmentioning
confidence: 99%
“…The corrosion of maraging steels in acidic solutions results mainly during the acid cleaning, where the scales and corrosion products that form on the steel surface and cause a negative effect on the performance of the steel equipment must be cleaned using an acidic pickling solution. In this regard, sulfuric acid is one of the most aggressive acids for iron and its alloys and is often used during cleaning, pickling, descaling, acidizing, and so forth .…”
Section: Introductionmentioning
confidence: 99%
“…The corrosion of maraging steels in acidic solutions results mainly during the acid cleaning, where the scales and corrosion products that form on the steel surface and cause a negative effect on the performance of the steel equipment must be cleaned using an acidic pickling solution. In this regard, sulfuric acid is one of the most aggressive acids for iron and its alloys and is often used during cleaning, pickling, descaling, acidizing, and so forth [2,10].…”
Section: Introductionmentioning
confidence: 99%